PERSEPSI SISWA TERHADAP KONDISI PENCAHAYAAN RUANG KELAS DI WILAYAH MALANG - Wibowo, Alvia Nayla; Muhammad Aris Ichwanto; Andyka Dimas Ardiansyah; Annisa Widhi Istiqomah; Tee Tze Kiong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Classroom lighting is one of the factors that influences students’ learning comfort. Poor lighting conditions can make students have difficulty concentrating, reading, and writing, as well as causing them to feel tided more quickly. This study aims to determine students’ perceptions of classroom lighting conditions and their effect on learning comfort in the Malang Raya area. This study used a quantitative method with a survey approach. Data were collected trough questionnaires distributed to junior and senior high school students in Malang Raya. The questionnaire used a four-point likert scale covering two variables, namely classroom lighting conditions and students’ learning comfort. The data were analyzed descriptively. The result showed that most students perceived classroom lighting conditions as inadequate. The majority of respondents stated that the classroom was not bright enough, the light distribution was uneven, and the lighting from windows and lamps had not optimally supported learning activities. These conditions caused students to feel uncomfortable while studying, have difficulty concentrating, experience problems in reading, writing, and seeing the board clearly and feel tired more quickly. Therefore, classroom lighting needs to be improved through better window arrangement, the use of appropriate lamps, and more even light distribution in the classroom.